Geographic variability of fatal road traffic injuries in Spain during the period 2002-2004: an ecological study - Jimenez-Puente Alberto; Perea-Milla Emilio; Rivas-Ruiz Francisco (BMC, 2007)
Abstract Background The aim of the present study is to describe the inter-province variability of Road Traffic Injury (RTI) mortality on Spanish roads, adjusted for vehicle-kilometres travelled, and to assess the possible role played by the following explicative variables: sociodemographic, structural, climatic and risk conducts. Methods An ecological study design was employed. The mean annual rate of RTI deaths was calculated for the period 2002-2004, adjusted for vehicle-kilometres travelled, in the 50 provinces of Spain. The RTI death rate was related with the independent variables described above, using simple and multiple linear regression analysis with backward step-wise elimination. The level of statistical significance was taken as p < 0.05. Results In the period 2002-2004 there were 12,756 RTI deaths in Spain (an average of 4,242 per year, SD = 356.6). The mean number of deaths due to RTI per 100 million vehicle-kilometres (mvk) travelled was 1.76 (SD = 0.51), with a minimum value of 0.66 (in Santa Cruz de Tenerife) and a maximum of 3.31 (in the province of Lugo). All other variables being equal, a higher proportion of kilometres available on high capacity roads, and a higher cultural and education level were associated with lower death rates due to RTI, while the opposite was true for the rate of alcohol consumers and the road traffic volume of heavy vehicles. The variables included in the model accounted for 55.4% of the variability in RTI mortality. Conclusion Adjusting RTI mortality rates for the number of vehicle-kilometres travelled enables us to identify the high variability of this cause of death, and its relation with risk factors other than those inherent to human behaviour, such as the type of roads and the type of vehicles using them.